Geospatial Assessment of Road Pavement Distress at Jahangirnagar University Campus - Bibi, Hafsa; Sanzana, Surovi; Mahib, Reza; K M Asif Iqbal, Akash; Khan Sarfaraz, Ali; Khandakar Hasan, Mahmud (INTI International University, 2025)
This study assesses the types, causes, and spatial distribution of pavement distress across six key road segments of the JU campus, aligning with the objectives of SDG 9 (Industry, Innovation, and Infrastructure) and SDG 11 (Sustainable Cities and Communities) to promote resilient and sustainable infrastructure systems. A mixed-method approach was employed, integrating direct field observation, photographic documentation, literature review, and geospatial mapping. Pavement distresses were classified into eight major categories: thermal cracking, warping cracking, longitudinal cracking, bleeding, stripping, raveling, pumping, and blistering. GPS coordinates were recorded using handheld devices to create georeferenced maps illustrating the spatial distribution of distress points. Data from six road sections—covering a total of 987.3 square meters—revealed 206 distress cases, with stripping (47), thermal cracking (39), and raveling (37) as the most prevalent types. These conditions were primarily influenced by temperature fluctuations, drainage inefficiencies, and material aging. Findings emphasize the necessity of regular pavement monitoring, improved drainage design, and the use of durable construction materials to enhance the resilience and longevity of campus road infrastructure. The study contributes to the national and institutional pursuit of sustainable transport and infrastructure management in line with SDG 9 and SDG 11, supporting safer, more sustainable, and inclusive mobility within educational environments